KEMAMPUAN MAHASISWA PGSD MEMBUAT MEDIA PEMBELAJARAN SEKOLAH DASAR - Radot Fransisca Hayati Siregar; Harmony Tampubolon (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The teacher as an educator creates situations so that students experience the learning process. Learning is a process of changing behavior that occurs as a result of external stimulation. Learning involves various elements in it, in the form of the physical and psychological conditions of the person studying. This type of research is qualitative research. Qualitative research is research intended to understand the phenomena experienced by research subjects, producing descriptive data in the form of written or spoken words from people and observed behavior. In this way, it can be said that this research is descriptive qualitative in nature. Discussion Results Learning media planning is an integral part of the school program, therefore it needs to involve all school components, both internal and external school personnel. It is hoped that the preparation of the media program can run in line with the learning program that has been created so that it can make a positive contribution to learning. Media management process learning must go hand in hand with the school program, it is necessary to form a learning media management/manager in elementary schools who is responsible for administering all activities related to learning media management. Understanding and knowledge about media management is important for officers in planning media programs, classifying media, grouping media based on the conditions of each school or based on certain subjects so that the media can be used optimally in the classroom and in storage areas.